Effect of Plastic Mulch Colour on Growth, Fruiting and Fruit Quality of Strawberry under Polyhouse Cultivation - Sharma, N. C.; Sharma, S. D.; Spehia, R. S. (International Journal of Bio-resource and Stress Management, 2023)
The field experiment was conducted during 2007-09 to study the effect of plastic mulch colour on growth, fruiting and fruit quality of strawberry under polyhouse cultivation. All three coloured plastic mulches (black, red and yellow) significantly increased the growth of strawberry plants as compared to control during both the years of study, but did not differ significantly among themselves with respect to plant growth. Red plastic mulch significantly extended the duration of flowering and fruiting and improved the fruit set as compared to control and black plastic mulch. Considerably higher yields, fruit size & weight and better fruit chemical composition (total soluble solids, total sugars, reducing sugars, ascorbic acid and anthocynin contents) were recorded in the plants mulched with red plastic as compared to black plastic mulch and no mulch (control). Though red plastic mulch was statistically at par with yellow plastic mulch with respect to all the parameters recorded during both the years of study but red plastic sheet was found to be most effective for increasing yield and improving fruit quality of strawberry under polyhouse cultivation.